Effect of the Methicillin-Resistant Staphylococcus aureus Nasal Polymerase Chain Reaction on Vancomycin Days and Clinical Outcomes in Pneumonia. (4th October 2017) - Hendon, Natalie; Nelson, Brian
Abstract: Background: Previous studies have demonstrated that the methicillin-resistant Staphylococcus aureus (MRSA) nasal polymerase chain reaction (PCR) assay has a high negative predictive value for MRSA pneumonia, and that a negative result may be used to guide antibiotic de-escalation. Despite increasing use in clinical practice, limited data exist regarding the impact of nasal MRSA testing on the duration of MRSA-directed therapy and patient outcomes. This study evaluated the effect of the MRSA nasal PCR result on vancomycin days and clinical outcomes in patients treated for pneumonia with empiric vancomycin therapy. Methods: A retrospective study of adult inpatients with an MRSA nasal PCR assay ordered between January 2015 and September 2015 was conducted. Patients with confirmed or presumed pneumonia and who were treated with empiric vancomycin therapy were included. Outcomes were compared for patients with a negative vs. a positive MRSA nasal PCR result. The primary outcome was the number of days of vancomycin therapy. Secondary outcomes included restart of vancomycin within 7 days, length of hospitalization, 30-day readmission, 30-day mortality, and predictive value of the MRSA PCR assay. Analyses were performed for the overall cohort and a propensity score-matched cohort. Results: 324 patients were included. In the overall cohort, the median duration of vancomycin therapy was 3 (interquartile range [IQR] 2–6) days in the negative MRSA nasal PCR group ( n = 282) and 6 (IQR 4–9) days in the positive nasal PCR group ( n = 42), P < 0.01. In the propensity score-matched cohort, the median number of vancomycin days was 3 (IQR 2–5) and 5 (IQR 4–8.5) in the negative ( n = 137) and positive ( n = 39) nasal PCR groups, respectively, P < 0.01. This difference persisted in an additional analysis of only patients with no positive respiratory cultures. No significant differences were observed in any secondary outcomes. The MRSA PCR assay demonstrated a positive predictive value of 45% and a negative predictive value of 98%. Conclusion: A negative MRSA nasal PCR correlated with fewer days of vancomycin therapy without negatively impacting other clinical outcomes. The use of the MRSA nasal PCR assay may reduce the duration of MRSA-active therapy in PCR-negative patients. Disclosures: All authors: No reported disclosures.